PSYCHOLOGICAL DESCRIPTION OF THE CONCEPT OF EMOTIONAL INTELLIGENCE (Spectrum Journal of Innovation, Reforms and Development, 2022)
In this article, psychological descriptions of the emergence of emotional intelligence, various studies on the concept of emotional intelligence, the structure of emotional intelligence, emotional intelligence and personality, the conditions for the development of emotional intelligence, and the psychological character of such concepts as emotional competence have been revealed.